ANALISIS PENGENDALIAN KUALITAS DENGAN METODE SIX SIGMA-DMAIC DALAM UPAYA MENGURANGI KECACATAN PRODUK REBANA PADA UKM ALFIYA REBANA GRESIK - Rozi, Muhammad Fahrur; Izzah, Nalul (Universitas Dr. Soetomo, 2019)
Competition in the business world that is increasingly stringent encourages companies to improve the quality of products produced.One way to reduce the level of product defects.The purpose of this study is to get the value of the product defect and improve the cause of the defect. The method used is Six Sigma DMAIC. This research was conducted in Alfiyah Rebana Gresik UKM, which is a business engaged in making tambourines. From the results of the study, it can be seen that the quality of tambourine produced by the company is quite good, namely the number of defective products of 146 tambourines, with a level of sigma 2.5 with the possibility of damage of 144,835 tambourines for a million production (DPMO). Based on the Pareto diagram, the most common level of disability occurs in eruptions, cracks, and sagging defects. Based on the diagram of fish bone or cause and effect diagram, the improvement that must be done is to make improvements to human, machine and material factors